Pengaruh Fitur Dan Kemudahan Penggunaan Terhadap Kepuasan Pengguna Aplikasi Si Rekap KPU - Rony Kriswibowo; Rusina Widha Febriana; Johan Suryo Prayogo; Putri Ariatna Alia (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2024)
This study aims to examine the effect of features and ease of use on user satisfaction of the Si Rekap KPU Application used in supporting the vote counting and recapitulation process in the 2024 Election. The research method uses a quantitative approach with an experimental design. Data was collected through a questionnaire distributed to 75 KPPS officers from the East Java region who had carried out the vote counting and recapitulation process in the 2024 Election using the Si Rekap KPU Application. The questionnaire was used to obtain data on perceived ease of use, usefulness, and acceptance of application information technology. The results showed that the ease of use and usefulness of application features had a significant positive effect on user satisfaction, with a contribution of 70% and 73%, respectively. Acceptance of application information technology by users also has a significant positive effect on user satisfaction with a contribution of 75%. Based on these results, it can be concluded that feature improvements, ease of use, and building user acceptance are needed to increase user satisfaction with the Si Rekap KPU Application in supporting the election process. Application improvements based on evaluation results are expected to optimize its performance.